Biologia reprodutiva de cinco espécies ornamentais de Apistogramma (Teleostei: cichlidae) da reserva de desenvolvimento sustentável Amanã-Amazonas - Rocha, Ana Carolina Prado Valladares da (Instituto Nacional de Pesquisas da Amazônia - INPA, 2009)
The species of Apistogramma genus is widely spread out in the ornamental fish trade due to their color diversity, easy rear and breeding in captivity. The survey for ornamental fish carried out at the Reserve of Sustainable Development Amanã, registered the occurrence of five species of the Apistogramma genus in the region. These species were selected for this study with the objective to determine their reproductive tactics and the structure of their population. For each species the reproductive cycle was described as well as sex-ratio by month and size, the average length at first sexual maturation, spawning period and type, length/weight relationship and condition were determined. Samplings were carried out bimonthly from February/2006 to February/2007, in streams of the RDS Amana. A total of 1769 specimens of A. agassizii, 479 of A. bitaeniata, 121 of A. eunotus, 490 of A. pertensis and 645 of A. hippolytae were analyzed. Size at sexual maturity (L 50 ) for females were as follows A. agassizii: 21.9 mm; A. bitaeniata: 25.5 mm; A. eunotus: 26.6 mm, A. pertensis: 27.2 and A. hippolytae 27.7 mm. Sex-ratio for A. eunotus and A. pertensis was always 1:1 throughout the year, however the other species presented differences favorable to females or males in different months of the year. As for gonadal development five different stages were observed for both sexes of all species: immature, maturation, ripe, spent and resting, the latter being found only for females. Direct observation and histological techniques indicated that all species show total spawning and the presence of oocytes at the perinuclear phase on the testis, except for A. agassizii. This study indicates that these species must be dealt with caution as much as management is concerned and the possibility of sex reversal process for A. bitaeniata, A. eunotus, A. pertensis and A. hippolytae.
Keywords: Ciclídeos; Peixes ornamentais; Reprodução de Apistogramma